Analysis self-regulation model based on belief in self-care in type 2 diabetes mellitus patients - Uly, Nilawati; Safruddin; Fadli; Eka Yulianita, Marisna; Batupadang, Michael (Journal of the Pakistan Medical Association, 2025)
Objective: To evaluate the efficacy of the self-regulation model based on belief to enhance the ability of individuals with type 2 diabetes mellitus to take care of themselves. Method: The survey-based study was conducted in South Sulawesi, Indonesia, from May to August 2023, and comprised type 2 diabetes mellitus patients of either gender whose blood glucose level was >200mg/dl. The survey comprised multiple questionnaires exploring the impact of exogenous variables on endogenous variables. Data was analysed using Structural Equation Modelling-Partial Least Squares method. Results: Of the 180 patients, 97(53.9%) were women and 83(41.6%) were men. The overall mean age was 55.8±6.55 years. Of the total, 110(61.1%) patients experienced complications in the form of hypertension or stroke, and 70(38.9%) were without complications. Characteristic factors influenced problem interpretation (p=0.016) and health (p=0.024). Social support factors influenced problem interpretation (p=0.018) and health (p=0.046). Health service factors influenced problem interpretation (p=0.024) and health (p=0.006). Interpretation of problems in illness had an influence on health (p=0.035) and beliefs (p=0.014). Coping had a significant influence on self-care (p=0.001). Conclusion: In order for patients to set goals and take the necessary steps to raise their awareness of performing self-care, health workers must be encouraged to increase patient confidence on solving health problems. This will have an impact on controlling blood glucose levels and preventing disease complications. Key Words: Belief, Self-regulation, Self-care, Type 2 diabetes mellitus.